News Media Trends in the Framing of Immigration and Crime, 1990–2013. (8th August 2019) - Harris, Casey T; Gruenewald, Jeff
Abstract: Few social problems engender as much public and political debate as the alleged link between immigration and crime. Contrary to the findings of much empirical literature, the majority of the public believe that immigration increases crime and that the foreign born are especially prone to offending. Among many factors, the way prominent news media describe the immigration-crime link may help explain the disconnectedness of scholarship and public opinion over the past several decades. Using a unique database of over 2, 200 news stories drawn from among the highest circulation national papers for 1990 through 2013, the current study employs time-series trend analyses to examine the prevalence of different media frames used to explain the immigration-crime link and whether those frames have changed systematically over time. Our results reveal that most immigration-crime news stories describe immigrants as especially crime-prone or as increasing aggregate crime rates. Moreover, this framing has increased in prevalence over time, as have narratives inaccurately describing undocumented immigration as a crime itself, while framing immigrants as victims of crime has declined significantly over the 1990–2013 period. These changes occurred systematically in only some newspapers. We discuss implications for research, policy, and the public engagement of scientific evidence.